2018
DOI: 10.1088/1748-9326/aaa4fc
|View full text |Cite
|
Sign up to set email alerts
|

Resource requirements of inclusive urban development in India: insights from ten cities

Abstract: This paper develops a methodology to assess the resource requirements of inclusive urban development in India and compares those requirements to current community-wide material and energy flows. Methods include: (a) identifying minimum service level benchmarks for the provision of infrastructure services including housing, electricity and clean cooking fuels; (b) assessing the percentage of homes that lack access to infrastructure or that consume infrastructure services below the identified benchmarks; (c) qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…For example, Nagpure et al . (2018) showed that per capita electricity use in the highest 20% income stratum is 5.5 times that of the lowest income stratum 29 . The effectiveness of this approach is evaluated by comparing against utility reported data at the city level (see Technical Validation).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Nagpure et al . (2018) showed that per capita electricity use in the highest 20% income stratum is 5.5 times that of the lowest income stratum 29 . The effectiveness of this approach is evaluated by comparing against utility reported data at the city level (see Technical Validation).…”
Section: Methodsmentioning
confidence: 99%
“…However, savings in the cost of horizontal infrastructure requirements (streets and pipes) can reliably be estimated with knowledge about the geometries and spatial layout of street networks, as can savings on construction materials per square foot when transitioning from single-story to high-rise construction. These are documented in multiple countries and literatures (Nagpure, Reiner, and Ramaswami 2018).…”
Section: Cities In Developing Countriesmentioning
confidence: 99%
“…Similar influences in developing economies such as China and India have also been documented in a few cases. For example, moving from single-story to high-rise construction in India can result in material use reduction of around 30 percent; infrastructure pipe network requirements in Delhi range from 1.4 m to 5.2 m sewerage piping per household in various neighborhoods based on density and spatial arrangements (Nagpure, Reiner, and Ramaswami 2018). A single study in China has found that horizontal infrastructure costs may be reduced by 50 percent in a compact growth scenario.…”
Section: Section 5 Conclusion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations